A detailed mutational analysis of Vmw110, a trans-acting transcriptional activator encoded by herpes simplex virus type 1. - Everett, R D (1987)
Viral genes expressed during infection of tissue culture cells by herpes simplex virus type 1 (HSV-1) can be divided into three broad temporal groups called immediate-early (IE), early and late. Prior expression of IE gene products is required before later classes of genes can be transcribed. Using cloned copies of viral genes in plasmid vectors, it has been shown that the products of IE genes 1 and 3 (Vmw110 and Vmw175) can activate transcription from both viral and cellular promoters in short-term transfection assays. The effects of these two IE gene products are markedly synergistic in HeLa cells; the activation observed with both genes present is about 20 times that observed with Vmw175 alone. The mechanism of this activation and the properties of the IE proteins that are required are not well understood. This paper describes the construction of a large number of in-frame insertion and deletion mutations in a plasmid-encoded copy of IE gene 1. The ability of the mutant Vmw110 polypeptides to activate gene expression (in the presence of Vmw175) from the HSV-1 glycoprotein gD promoter linked to the chloramphenicol acetyl transferase gene was studied. The results show that the structural integrity of at least five regions of the polypeptide are important for its function in the presence of Vmw175.